Fructo-Oligosaccharides Modify Human DC Maturation and Peanut-Induced Autologous T-Cell Response of Allergic Patients In Vitro - Hayen, Simone M.; Knulst, André C.; Garssen, Johan; Otten, Henny G.; Willemsen, Linette E. M. (Frontiers in Immunology, 2021)
Background: Dendritic cells (DCs) play an important role in antigen presentation, and are an interesting target for immune-modulation in allergies. Short- and long-chain fructo-oligosaccharides (scFOS/lcFOS, FF) have immunomodulatory capacities, and may influence the outcome of DC antigen presentation. Objective: This study investigated the effect of FF during DC maturation and allergen presentation using cells of peanut-allergic patients in an autologous DC-T cell assay. Methods: CD14+ and CD4+ T cells were isolated from peanut-allergic patients. CD14+ monocytes were differentiated into immature DCs (imDCs), and matured (matDCs) in the presence or absence of crude peanut-extract (CPE) and/or FF, and co-cultured in an autologous DC-T cell assay. T cell polarization, proliferation and cytokine production were measured. Results: Expression of maturation surface molecule markers on matDCs was not affected by CPE and/or FF. By contrast, the IL-10 secretion by matDCs increased compared to imDCs, upon exposure to CPE and FF compared to CPE alone. Also the IP-10 secretion increased in CPE/FF-matDCs compared to imDC. CPE-matDCs enhanced IL-13 release in the DC-T-cell assay and Treg polarization in presence or absence of FF. CPE/FF-DCs tended to increase the Treg/Th1 and Treg/Th2 ratios compared to matDCs. The proliferation of both Treg and Th2 cells tended to increase when T cells were co-cultured with CPE-matDCs compared to matDCs, which became significant when CPE-matDCs were also exposed to FF and a same tendency was shown for Th1 proliferation. Conclusion: Only in the presence of FF, CPE-matDCs produced increased regulatory and Th1-related mediators. CPE-matDCs modified T cell polarization and proliferation, and additional exposure to FF tended to enhance Treg/Th2 and Treg/Th1 ratios instructed by CPE/FF-matDCs. However this effect was not strong enough to suppress CPE-matDCs induced IL-13 release by Th-cells. This indicates the ability of FF to modify DC maturation in the presence of an allergen supporting a more Treg/Th1 prone direction of the successive allergen specific Th2 cell response.